Serum Levels of TIMP‐3, LIPC, IER3, and SLC16A8 in CFH‐Negative AMD Cases. Issue 8 (18th April 2017) - Sharma, Kaushal; Tyagi, Rahul; Singh, Ramandeep; Sharma, Suresh Kumar; Anand, Akshay
ABSTRACT: AMD is a complex eye disease predominantly occurring in aged population. Till now about 53 genetic loci have been found to be associated with the AMD pathology. AMD pathogenesis is being increasingly known to progress through mechanisms independent of the CFH mediated pathway. Therefore, our aim for current study was to examine the genes by analyzing their expression levels in AMD. We recruited about 50 AMD and same number of age matched controls. We analyzed the CFH duplication and deletion by multiplex ligation probe amplification (MLPA) and found no duplication and deletion in CFH gene in AMD patients. We also estimated the IER‐3, SLC16A8, LIPC, and TIMP‐3 expression levels in both CFH‐negative AMD cases (i.e. no duplication and deletion in CFH gene) besides examining these in AMD and controls. We found that the expression level of LIPC, SLC16A8, and TIMP ‐3 was significantly associated with AMD pathology in both groups ( LIPC : P  = 0.008, SLC16A8 : P  < 0.001, TIMP‐3: P  < 0.001, respectively). However, we did not find any significant difference in IER‐3 levels in AMD and controls. Therefore, the evidence from current study, suggests that AMD pathology may be mediated through mechanistic pathways linked to other genetic loci. J. Cell. Biochem. 118: 2087–2095, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The article demonstrated LIPC, SLC16A8, TIMP‐3, and IER‐3 expression levels in AMD pathology.